2020
DOI: 10.18632/aging.103750
|View full text |Cite
|
Sign up to set email alerts
|

Jinmaitong ameliorates diabetic peripheral neuropathy in streptozotocin-induced diabetic rats by modulating gut microbiota and neuregulin 1

Abstract: Jinmaitong (JMT), a compound prescription of traditional Chinese medicine, has long been used as a therapy for diabetic peripheral neuropathy (DPN). However, the neuroprotective mechanisms of JMT and its effect on gut microbiota remained unknown. Here, we examined the effects of JMT on behavior, pathomorphology and gut microbiota in streptozotocin (STZ)-induced DPN rats. Compared to distilled water administration, JMT reversed decreases in mechanical withdraw threshold and intraepidermal nerve fiber density, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…The DM animal model induced with SZT is usually used for DPN study at home and abroad [ 25 , 26 ]. It has been generally agreed that the blood glucose value is greater than 16.65 mmol/L as a model for DM rats [ 27 ]. Electrophysiological examination is a sensitive index for early diagnosis of DPN.…”
Section: Related Workmentioning
confidence: 99%
“…The DM animal model induced with SZT is usually used for DPN study at home and abroad [ 25 , 26 ]. It has been generally agreed that the blood glucose value is greater than 16.65 mmol/L as a model for DM rats [ 27 ]. Electrophysiological examination is a sensitive index for early diagnosis of DPN.…”
Section: Related Workmentioning
confidence: 99%
“…This finding indicated that gut microbiota imbalance also existed in DPN, which was consistent with the previous studies. 20,21 Parabacteroides species can transform bile acids and enhance secondary bile acid content, such as TUDCA. 11 Wang et al proved that TUDCA content was positively correlated with Parabacteroides in DPN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, plasma TMAO levels in DR individuals were significantly higher than those in non-retinopathy T2DM individuals, and its levels were positively correlated with the incidence of DR, indicating that TMAO might be involved in the development of DR ( Liu W. et al, 2021 ). Xie et al discovered that STZ-induced DPN rats showed gut microbiota dysbiosis, which was characterized by enrichment of Klebsiella , Coprococcus , Prevotella and other bacterial taxa ( Xie et al, 2020a ). Importantly, The TCM compound Jinmaitong improved the phenotype of peripheral neuropathy by regulating the gut microbiota composition and increasing the levels of neuregulin 1 (NRG1) in DPN rats.…”
Section: Gut Microbiota and T2dmmentioning
confidence: 99%